A Study of Quranic Allegory, Decorative Ornaments in Female Attire miniature at museum and Architecture: Dᾱī’ Angᾱ Mausoleum & Mosque in Lahore Punjab (Al-Qamar, 2021)
Religion have a significant aspect in changing culture and practices of region where humans live. All aspects of existence are represented by religion. This gave bases to representation of women through her dressing and house hold shores. This have been addressed in holy Quran. In which women and her representation at different areas are done in which her covering and dressing. Woman is the created by God for Adam’s employer and companion to step into humanly life to begin a family. He created woman like a gem inside the sea shell. Inspiration and interpretation of verses were adopted in Mughal aesthetic in multiple ways of art and architecture in Lahore. There is variety in adaption and effect of continuous invasions at current place where Lahore is situated in Punjab Pakistan. These cultural integration dominated as permanent marks in connection with females and there representation in Mughal remnants. Quran addresses female and there rights through verses and references. Some address directly to rights of female within society. Secondly there are metaphoric presentation of female aesthetics. One of its example is Mughal architecture Dᾱī’ Angᾱ Mausoleum Gulabi Bagh. Which is construction for female wet nurse of Shajahān son of Jahangīr.
Keywords: Attire; Quran; Female; inspiration; art; ornamental design